Major incident simulation in Rwanda: A report of two exercises - Gabin Mbanjumucyo; Ernest Nahayo; Noah Polzin-Rosenberg; Giles N. Cattermole (African Journal of Emergency Medicine, 2018)
Introduction: Healthcare systems must be equipped to handle major incidents. Few have been described in the African setting, including in Rwanda. The purpose of this case report was to describe and discuss two major incident simulations in Rwanda with different challenges. Case report: We report two recent major incident exercises conducted in Rwanda, in 2017. The exercises exemplify two different types of multiple casualty incidents requiring the deployment of extra-ordinary resources, one due to the location of the incident (off-shore), and the other due to the large volume of casualties. Both exercises required extensive multi-agency planning and training beforehand, as part of an increasing awareness of the need for preparedness for these types of incidents. Conclusion: The exercises demonstrated the need for a standardised, physiological method of triage based on clinical needs; this is in order to maximise the number of lives saved. Triage training should be an integral part of further major incident exercises, which should be conducted regularly. Keywords: Major incidents, Triage, Rwanda